FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KETIDAKBERHASILAN ASI EKSKLUSIF PADA IBU MENYUSUI DI PUSKESMAS YOSOMULYO KOTA METRO - Yuliawati Yuliawati; sadiman sadiman; Septi Widiyanti; Linda Anisa (JOEL: Journal of Educational and Language Research, 2022)
The World Health Organization WHO, recommends to mothers around the world to exclusively breastfeed their babies for the first 6 (six) months after the baby is born to achieve optimal growth, development and health. At the Yosomulyo Health Center, 45.3% were not given exclusive breastfeeding. The purpose of this study was to determine the factors associated with the ineffectiveness of exclusive breastfeeding in breastfeeding mothers at the Yosomulyo Community Health Center. Quantitative research method with cross sectional design. The total population of breastfeeding mothers at the Yosomulyo Health Center is 336 nursing mothers. The sample size was determined based on the Lemeshow formula obtained by 75 respondents. The sampling technique used is simple random sampling. Collecting data using a questionnaire. The analysis obtained the p-value of each variable, namely: knowledge with a p-value of 0.009, parity with a p-value of 0.000 and family support with a p-value of 0.000. The conclusion is that there is a relationship between knowledge, parity, and family support with the inability of exclusive breastfeeding for breastfeeding mothers at Yosomulyo Public Health Center, Metro City.